1994
DOI: 10.1002/actp.1994.010450202
|View full text |Cite
|
Sign up to set email alerts
|

Side chain polyrotaxanes: 2. Functionalized polysulfone with non‐covalently anchored cyclodextrins in the side chains

Abstract: The synthesis of a new side-chain polyrotaxane containing P-dimethyl cyclodextrin rings is described. The rotaxane side groups are attached via amide functions at an aromatic polysulfone. Some characteristics ofthe polyrotaxane are compared with those of a corresponding guest model compound. It is found that the T, value, the solubility in chloroform and acetone, some 'H-NMR shifts and the GPC maximum are significantly influenced by the non-covalently anchored cyclodextrin rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 11 publications
0
46
0
Order By: Relevance
“…Furthermore, the preparation and polymerization of equimolar cyclodextrin complexes of commercial standard monomers like styrene 1 and methyl methacrylate (MMA have been described. It was also shown that the precipitation polymerization of a cyclodextrin complex of a poorly water-soluble monomer like MMA can be described by kinetic equations similar to those for the classical polymerization in solution [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the preparation and polymerization of equimolar cyclodextrin complexes of commercial standard monomers like styrene 1 and methyl methacrylate (MMA have been described. It was also shown that the precipitation polymerization of a cyclodextrin complex of a poorly water-soluble monomer like MMA can be described by kinetic equations similar to those for the classical polymerization in solution [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In our group, we have recently investigated the radical polymerization of cyclodextrin complexed methacryl derivatives and some other types of monomers [5][6][7][8][9][10][11][12][13] . Emulsion polymerization of vinyl compounds using cyclodextrins has also been described [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Gibson et al studied solvent-switchable polyrotaxanes utilizing polyurethenes and crown ether [16][17] . Ritter et al studied sidechain polyrotaxanes utilizing CyDs and a polymethacrylate or poly(ether sulfone) as a main chain [18][19][20] . Harada et al investigated macromolecular recognition by CyDs with poly(ethylene glycol) (PEG), poly(propylene glycol) (PPG), poly(isobutylene), and polyesters as a family of polyrotaxanes [21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%